ANALISIS PELAKSANAAN PROMOSI PENJUALAN DALAM MENINGKATKAN VOLUME PENJULAN PONSEL PADA SAHABAT KOE PONSEL PEKANBARU - Dani, Ilfan; Farida, Lena (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Sales promotion is a series of actions to get the attention of consumers and provide stimulus to prospective customers. integrative designed to promote and offer items that are considered by different customers in the things that are important and unique to them. Sales Volume is the end result achieved by the company from the sales generated by the company. Sahabat Koe Ponsel as one of the companies selling goods should be able to survive from the times to increase competition. in order to create increased sales volume, there for Sahabat Koe Ponsel Companion has a business concept in the form of sales of goods and mobile phone accessories to prospective customers and consumers remains the goal, to try to continue to get closer to its customers. These results indicate that the Implementation Analysis Sales Promotion effect on Increased Sales Volume. Judging from the responses of respondents who chose shows that using sales promotions on the package price will further optimize the increase in sales volume on the Sahabat Koe Ponsel. Keywords: Sales Promotion, Sales Volume